Imaging of the Aorta A Practical Guide for Radiologists - Carbone, Iacopo; Farina, Davide; Nardis, Pier Giorgio; Bellini, Davide; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This book provides younger radiologists with a practical guide to aortic imaging, from acquisition to reporting. It discusses the pros and cons of the different available techniques and offers tips for the optimization of acquisition protocols and it covers the most frequent aortic pathologies, from a diagnostic and interventional point of view. Report building is discussed starting from standardized terminology; for each pathology, the book lists, in a simple and schematic way, the key points that must be included in the report of a cross-sectional study. Checklists used by clinicians and radiologists in routine practice are also included, and iconography is enriched by numerous stand-alone images. The Authors have long-standing experience in cardiovascular imaging and interventional procedures and with this publication they are providing a useful guide in everyday clinical practice. This book is a translation of an original Italian edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
1 Anatomy and imaging techniques -- 2 Aorta on chest X-ray -- 3 Aortic aneurysms: pretreatment evaluation -- 4 Aortic aneurysms: follow up -- 5 Acute aortic syndrome -- 6 Inflammatory diseases of the aorta -- 7 Congenital anomalies of thoracic aorta: an overview -- 8 Taking it to the test - clinical cases.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Radiology; Interventional radiology; Cardiology; Blood-vessels -- Surgery; Radiology; Interventional Radiology; Cardiology; Vascular Surgery